Performance Analysis of Grid Topologies and RANS Turbulence Models in Predicting Aerodynamic Drag Coefficient at Zero-yaw for an Artillery Projectile - A. Ferfouri; D. D. Jerković; N. Hristov; A. V. Kari; T. Allouche (Journal of Applied Fluid Mechanics)
The present paper evaluates the performance of grid topologies and RANS turbulence models in predicting the aerodynamic drag coefficient of a 155mm artillery projectile by conducting steady-state computational research. The research is performed for Mach numbers from 0.5 to 3.0, assuming axisymmetric flow. Four distinct combinations of grid topology and turbulence model are investigated, where the O- and C-grid topologies are each paired with both the realizable k-ε and the SST k-ω models. Compared to the experimental data across the Mach number range, the combination of O-grid with k-ε model showed the smallest mean deviation of 1.64%, while the combination of O-grid with k-ω exhibited the largest mean deviation of 5.54%. In terms of drag component results, both turbulence models and grid topologies performed equally in predicting pressure and friction drag, with differences less than 6% in all Mach number cases. However, significant discrepancies were obtained in base drag prediction, especially between the two turbulence models, with differences reaching around 60% in the transonic regime. This was identified as the main contributor to the discrepancies in aerodynamic drag coefficient results among the four combinations. Furthermore, the findings indicate that the turbulence model selection impacts the zero-yaw drag prediction more than the grid topology, especially in the transonic and low supersonic cases.